(untitled) (Current Problems in Rail Vehicles, 2025)
This article examines the effect of tunnel passage on the internal noise level of a railway vehicle. Measurements were carried out on three different types of coaches during open track and tunnel runs, in accordance with the ČSN EN ISO 3381 standard. Microphones were placed in various parts of the vehicles, including boarding areas, inter-car gangways, and, in one case, the driver’s cab. The results show that the vehicle design—pressure-tightness and the number of floors—significantly affects the difference in sound pressure levels between open track and tunnel conditions. The largest differences were observed in double-deck coaches, while pressure-tight vehicles showed the smallest changes in noise levels. The findings may contribute to optimizing vehicle design in terms of acoustic comfort.